Regesten zur Geschichte der Juden in Österreich Band 5: 1405-1418 - Brugger, Eveline (Studien Verlag, 2022)
The remarkably high number of medieval sources on the history of Austrian Jews provide insights into the economic, legal, and social standing of the Jews as well as into how the Christian environment treated them. The sources collected in this volume give evidence of the policies towards the Jews of Dukes Wilhelm, Leopold IV, Ernst, Friedrich IV and Albrecht V as well as of the rulers of those territories that weren't under Habsburg rule during the period under study. Additionally, the source material allows for an analysis of the manifold Jewish-Christian interaction and the living conditions of the Jewish population. •Volume 1: Von den Anfängen bis 1338: https://e-book.fwf.ac.at/o:55 •Volume 2: 1339-1365: https://e-book.fwf.ac.at/o:58 •Volume 3: 1366-1386: https://e-book.fwf.ac.at/o:766 •Volume 4: 1387-1404: https://e-book.fwf.ac.at/o:1229 •Volume 5: 1405-1418: https://e-book.fwf.ac.at/o:1794